2020
DOI: 10.3390/biomedicines8010005
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to THC Alters M-Cell Development in Zebrafish Embryos

Abstract: Cannabis is one of the most commonly used illicit recreational drugs that is often taken for medicinal purposes. The psychoactive ingredient in cannabis is Δ9-Tetrahydrocannabinol (Δ9-THC, hereafter referred to as THC), which is an agonist at the endocannabinoid receptors CB1R and CB2R. Here, we exposed zebrafish embryos to THC during the gastrulation phase to determine the long-term effects during development. We specifically focused on reticulospinal neurons known as the Mauthner cells (M-cell) that are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Set-up was similar as described above. Following the experiment, larvae were stained with anti-RMO44 (Thermo Fisher Scientific, Waltham, MA, USA) and imaged using a Zeiss LSM 710 confocal microscope (Oberkochen, Germany) as described elsewhere 76 .…”
Section: Methodsmentioning
confidence: 99%
“…Set-up was similar as described above. Following the experiment, larvae were stained with anti-RMO44 (Thermo Fisher Scientific, Waltham, MA, USA) and imaged using a Zeiss LSM 710 confocal microscope (Oberkochen, Germany) as described elsewhere 76 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, locomotion studies also showed that the number of C-start escape responses to sound stimuli for THC and CBD exposed zebrafish larvae was severely reduced ( Ahmed et al 2018 ). Exposure to THC (6 mg L -1 ) for 5.25 to 10.75 hours post fertilization affected the zebrafish embryos’ mircofold cell axon diameter and their escape response dynamics to touch ( Amin et al 2020 ). Zebrafish muscle fibers had small but significant changes in the pattern of expression of nicotinic acetylcholine receptors and were slightly disorganized even though the muscles were largely intact ( Amin et al 2020 ).…”
Section: Toxicity and Impact On The Environmentmentioning
confidence: 99%
“…Exposure to THC (6 mg L -1 ) for 5.25 to 10.75 hours post fertilization affected the zebrafish embryos’ mircofold cell axon diameter and their escape response dynamics to touch ( Amin et al 2020 ). Zebrafish muscle fibers had small but significant changes in the pattern of expression of nicotinic acetylcholine receptors and were slightly disorganized even though the muscles were largely intact ( Amin et al 2020 ). However, qPCR results showed no obvious changes in the expression of mRNA of the nicotinic receptor subunit ( Amin et al 2020 ).…”
Section: Toxicity and Impact On The Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabinoid treatment altered synaptic activity at neuromuscular junctions (NMJs) and altered nicotinic acetylcholine receptor expression at NMJs [ 83 ]. Exposure to 6 mg/L THC during gastrulation, from 5.25 to 10.75 hpf slightly altered the axon diameter of Mauthner cells (M-cell), the neurons born during gastrulation and which are involved in escape response movements [ 85 ]. The muscle fibers of those larvae were slightly disorganized with subtle but significant changes in nicotinic acetylcholine receptor expression patterns [ 85 ].…”
Section: Zebrafish: a Model System To Study The Effect Of Marijuanmentioning
confidence: 99%